Chapter One - Instream wood functions as an ecosystem engineer in river ecosystem development following recent deglaciation in Glacier Bay National Park, Alaska - Klaar, Megan J; Clitherow, Leonie R; Titley, Alexandra; Gloyne-Phillips, Ian; Smith, Mark W; Maddock, Ian; Milner, Alexander M (Advances in ecological research, 2024)
The role of riparian vegetation in driving hydrogeomorphic development within rivers is increasingly recognised. Vegetation-mediated biotic-abiotic interactions are known to become dominant as landscapes develop, however to date the timescales and rates of these interactions remain poorly understood. Here, we outline how our ongoing research of river development in Glacier Bay National Park has allowed us to observe and quantify the role of instream wood in driving biotic-abiotic feedback mechanisms over a large spatiotemporal scale. Our research shows that the colonisation of riparian areas with small, relatively simple woody material (predominantly alder and willow boles) and its subsequent introduction into the river channel initiates the creation of hydrogeomorphic diversity which biotic communities are able to utilise. However, as riparian vegetation continues to develop through succession, the introduction of increasingly large and complex material (spruce and hemlock trees) exerts increasing control on instream conditions. This review highlights the role of instream wood in increasing river-terrestrial interactions, and incorporates instream wood into previous conceptual models related to fluvial biogeomorphological succession and ecosystem development within Glacier Bay.